We will discuss here how to find the sum of the squares of first n natural numbers.
Let us assume the required sum = S
Therefore, S = 1\(^{2}\) + 2\(^{2}\) + 3\(^{2}\) + 4\(^{2}\) + 5\(^{2}\) + ................... + n\(^{2}\)
Now, we will use the below identity to find the value of S:
n\(^{3}\)  (n  1)\(^{3}\) = 3n\(^{2}\)  3n + 1
Substituting, n = 1, 2, 3, 4, 5, ............., n in the above identity, we get
1\(^{3}\)  0\(^{3}\) = 3 . 1\(^{2}\)  3 ∙ 1 + 1
2\(^{3}\)  1\(^{3}\) = 3 . 2\(^{2}\)  3 ∙ 2 + 1
3\(^{3}\)  2\(^{3}\) = 3 . 3\(^{2}\)  3 ∙ 3 + 1
4\(^{3}\)  3\(^{3}\) = 3 . 4\(^{2}\)  3 ∙ 4 + 1
......................................
n\(^{3}\)  (n  1)\(^{3}\) = 3 ∙ n\(^{2}\)  3 ∙ n + 1
____ _____
Adding we get, n\(^{3}\)  0\(^{3}\) = 3(1\(^{2}\) + 2\(^{2}\) + 3\(^{2}\) + 4\(^{2}\) + ........... + n\(^{2}\))  3(1 + 2 + 3 + 4 + ........ + n) + (1 + 1 + 1 + 1 + ......... n times)
⇒ n\(^{3}\) = 3S  3 ∙ \(\frac{n(n + 1)}{2}\) + n
⇒ 3S = n\(^{3}\) + \(\frac{3}{2}\)n(n + 1) – n = n(n\(^{2}\)  1) + \(\frac{3}{2}\)n(n + 1)
⇒ 3S = n(n + 1)(n  1 + \(\frac{3}{2}\))
⇒ 3S = n(n + 1)(\(\frac{2n  2 + 3}{2}\))
⇒ 3S = \(\frac{n(n + 1)(2n + 1)}{2}\)
Therefore, S = \(\frac{n(n + 1)(2n + 1)}{6}\)
i.e., 1\(^{2}\) + 2\(^{2}\) + 3\(^{2}\) + 4\(^{2}\) + 5\(^{2}\) + ................... + n\(^{2}\) = \(\frac{n(n + 1)(2n + 1)}{6}\)
Thus, the sum of the squares of first n natural numbers = \(\frac{n(n + 1)(2n + 1)}{6}\)
Solved examples to find the sum of the squares of first n natural numbers:
1. Find the sum of the squares of first 50 natural numbers.
Solution:
We know the sum of the squares of first n natural numbers (S) = \(\frac{n(n + 1)(2n + 1)}{6}\)
Here n = 50
Therefore, the sum of the squares of first 50 natural numbers = \(\frac{50(50 + 1)(2 × 50 + 1)}{6}\)
= \(\frac{50 × 51 × 101}{6}\)
= \(\frac{257550}{6}\)
= 42925
2. Find the sum of the squares of first 100 natural numbers.
Solution:
We know the sum of the squares of first n natural numbers (S) = \(\frac{n(n + 1)(2n + 1)}{6}\)
Here n = 100
Therefore, the sum of the squares of first 50 natural numbers = \(\frac{100(100 + 1)(2 × 100 + 1)}{6}\)
= \(\frac{100 × 101 × 201}{6}\)
= \(\frac{2030100}{6}\)
= 338350
● Arithmetic Progression
From Sum of the Squares of First n Natural Numbers to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.